2022
DOI: 10.1186/s12909-022-03503-7
|View full text |Cite
|
Sign up to set email alerts
|

Impact of background music on the performance of laparoscopy teams

Abstract: Background Acoustic conditions in the operating room have different impacts on surgeon’s performance. Their effects on the performance of surgical teams are not well documented. We investigated if laparoscopic teams operating under pleasant acoustic conditions would perform better than under noisy conditions. Methods We recruited 114 surgical residents and built 57 two-person teams. Each team was required to perform two laparoscopic tasks (object t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…17,18 Disquieting evidence from studies around the world shows that dental students are three times more susceptible to deteriorating mental and physical health than the average college student. [19][20][21] Scientific evidence for the beneficial effect of music on surgeons' task performances was given in a study written by Lies and Zhang. 22 The plastic surgeries showed improved efficiency of skin repair in a wound closure model when trainees listened to background music during their activities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…17,18 Disquieting evidence from studies around the world shows that dental students are three times more susceptible to deteriorating mental and physical health than the average college student. [19][20][21] Scientific evidence for the beneficial effect of music on surgeons' task performances was given in a study written by Lies and Zhang. 22 The plastic surgeries showed improved efficiency of skin repair in a wound closure model when trainees listened to background music during their activities.…”
Section: Introductionmentioning
confidence: 99%
“…Depression and anxiety symptoms pose a threat to dental students coping capabilities 17,18 . Disquieting evidence from studies around the world shows that dental students are three times more susceptible to deteriorating mental and physical health than the average college student 19–21 …”
Section: Introductionmentioning
confidence: 99%
“…An objective evaluation of the subjectively experienced burden of the OR soundscape is challenging. Previous studies that have focused on the effect of sound on performance (i.e., surgery task performance) have found that only under extreme and unnatural conditions, such as dichotic listening to two pieces of music 14,15 , but not under more natural conditions, such as a single stream of OR sounds [16][17][18][19][20][21] , more mistakes in the surgery task were observable. However, medical personnel may strive to perform at high levels under adverse working conditions because mistakes can have serious consequences for the patient.…”
Section: Introductionmentioning
confidence: 99%